Educating for Pedagogical Competence Today - Gargiulo Labriola, Alessandra (Formazione & insegnamento, 2025)
The issue of competences goes beyond teaching practices linked to school performance and extends beyond a pedagogical culture reduced to the instrumental certification of knowledge, skills, and aptitudes. It implies the ability to consider the contexts of educational policies in which it may emerge as a pedagogical framework of educational responsibility. In this sense, competence can be defined as ‘pedagogical’ when it integrates knowledge and participation, contributing to heuristic perspectives in research with and for people, highlighting the value-laden dimensions of our constitutional and European values, such as citizenship and the common good. Its movement towards unexplored territories makes competence a frontier construct of the post-modern era, never reducible to possession but rather to development in the perspective of existential proximity, oriented towards possible futures. This contribution adopts a critical pedagogical stance towards the epistemic future of competence, using the metaphor of the pilgrim’s path to depict a person who not only embarks on a journey to find meaning but also, which is rare and precious, seeks relational and existential closeness with real people and things—a prelude to a genuine experience of change and the development of a responsible conscience. This journey, in the perspective of the capability approach, concerns the analysis of educational needs among socially vulnerable groups, inequalities, and poverty, calling for pedagogical efforts to move away from dominant views of history (individualism, distorted anthropocentrism, utilitarianism, rampant consumerism) and towards a new understanding of historical, personal, professional, and social events rooted in human rights and principles of justice, equity, equality, and an ethic of compassionate understanding of human dignity.